As Time Goes by: Understanding Child and Family Factors Shaping Behavioral Outcomes After Traumatic Brain Injury - Ewing-Cobbs, Linda; Montroy, Janelle J.; Clark, Amy E.; Holubkov, Richard; Cox, Charles S.; Keenan, Heather T. (Frontiers in Neurology, 2021)
Abstract Objective: To model pre-injury child and family factors associated with the trajectory of internalizing and externalizing behavior problems across the first 3 years in children with pediatric traumatic brain injury (TBI) relative to children with orthopedic injuries (OI). Parent-reported emotional symptoms and conduct problems were expected to have unique and shared predictors. We hypothesized that TBI, female sex, greater preinjury executive dysfunction, adjustment problems, lower income, and family dysfunction would be associated with less favorable outcomes. Methods: In a prospective longitudinal cohort study, we examined the level of behavior problems at 12 months after injury and rate of change from preinjury-12 months and from 12-36 months in children ages 4-15 years with mild to severe TBI relative to children with OI. A structural equation model framework incorporated injury characteristics, child demographic variables, as well as pre-injury child reserve and family attributes. Internalizing and externalizing behavior problems were indexed using the parent-rated Emotional Symptoms and Conduct Problems scales from the Strengths and Difficulties questionnaire. Results: The analysis cohort of 534 children (64% boys, M(SD) 8.8(4.3) years of age) included 395 with mild to severe TBI and 139 with OI. Behavior ratings were higher after TBI than OI but did not differ by TBI severity . TBI, higher pre-injury executive dysfunction, and lower income predicted the level and trajectory of both Emotional Symptoms and Conduct Problems at 12 months. Female sex and poorer family functioning were vulnerability factors associated with greater increase and change in Emotional Symptoms by 12 months after injury; unique predictors of Conduct Problems included younger age and prior emotional/behavioral problems. Across the long-term follow-up from 12 to 36 months, Emotional Symptoms increased significantly and Conduct Problems stabilized. TBI was not a significant predictor of change during the chronic stage of recovery. Conclusions: After TBI, Emotional Symptoms and Conduct Problem scores were elevated, had different trajectories of change, increased or stayed elevated from 12 to 36 months after TBI, and did not return to preinjury levels across the 3 year follow-up. These findings highlight the importance of addressing behavioral problems after TBI across an extended time frame.